Dinamika Peranan Politik Keturunan Arab di Tingkat Lokal - Burhan D. Magenda (Antropologi Indonesia, 2005)
The article focuses on the role of Indonesian of Arab descents in local politics, particularly in two provinces in Outer Islands, East Kalimantan and West Nusa Tenggara. While much have been researched on the role of Arab descents in national Politics such as studies by Hamid Algadri and Bisri Affendy, little is known about their roles in local politics. In East Kalimantan, Indonesian of Arab descents have played political roles up to the level of Vice Governor and other important positions, as far back as the Sultanates period in the 1950s. Similar important political role have also occurred in West Nusa Tenggara where Indonesian of Arab descents were the Chairman of Local Parliament (DPRD) and Assistant to the Governors, both in the1950s and 1960s. The important roles that have been played by Indonesians of Arab descents are made possible by their "local assimilation" to the local indigenous communities, both trough intermarriages; common living in the same residential areas; common Islamic beliefs and their integration into Indonesian political system after dissolution of Indonesian party of Arab descent (PAI) in the 1930s which have differentiated them from the political history of Indonesian of Chinese descent (peranakan Tionghoa). Key words: the Arab Indonesian; local politics; religious assimilation.